Gestión de la confiabilidad y optimización del consumo energético en sistemas de aire acondicionado en zonas residenciales (2019)
The purpose of this research report is to promote awareness of the use and maintenance of air conditioning equipment in residential spaces, which has a considerable impact on personal and environmental aspects, which justifies the relationship between reliability and consumption in the face of efficiency and effectiveness. Methodologically, it is an investigation under the pos-itivist paradigm, quantitative research approach. The survey technique was used, through the questionnaire, as an instrument, in the same way the observation with the purpose of expressing the degrees of intensity to prioritize characteristics of the process. Product of the investigation, stands out as results that, in residential areas of Cúcuta, the use and maintenance of the air con-ditioning equipment does not comply with basic standards, this derives a higher consumption of energy, affections to the health of the users, as well as contamination in spaces, which translates into economic and environmental costs.